1993
DOI: 10.1002/j.1460-2075.1993.tb05662.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a guanine nucleotide dissociation stimulator for a ras-related GTPase.

Abstract: ras‐related GTPases participate in signaling for a variety of cellular processes. The GTPases cycle between a GTP‐bound active state and a GDP‐bound inactive state. This cycling is partially controlled by guanine nucleotide dissociation stimulators (GDS, also known as exchange factors). We report on the molecular cloning of cDNAs encoding a new mammalian GDS protein, using sequences derived from the yeast ras GDS proteins as probes. The encoded protein stimulates the dissociation of guanine nucleotides from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
132
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 51 publications
1
132
0
Order By: Relevance
“…The ®rst 785 bases coded for a protein that had more than 95% amino acid identity with HHR23A, the human homologue of the yeast gene rad 23. The homology was abruptly lost after the ®rst 785 bases, and the following 1.4 kb showed 60% identity to the mouse cDNA sequence for ral-GDS (Albright et al, 1993). This result indicates that a fusion between two genes most likely occurred in the activation process.…”
Section: Oncogene Cdna Isolationmentioning
confidence: 85%
See 1 more Smart Citation
“…The ®rst 785 bases coded for a protein that had more than 95% amino acid identity with HHR23A, the human homologue of the yeast gene rad 23. The homology was abruptly lost after the ®rst 785 bases, and the following 1.4 kb showed 60% identity to the mouse cDNA sequence for ral-GDS (Albright et al, 1993). This result indicates that a fusion between two genes most likely occurred in the activation process.…”
Section: Oncogene Cdna Isolationmentioning
confidence: 85%
“…On the other hand the pathway mediated by Ral seems to activate phospholipase D (PLD) (Jiang et al, 1995) and a Ral e ector, named Ral BP1 (Cantor et al, 1995) or RIP 1 (Park and Weinberg, 1995), has rho-GAP activity, but its members had not been reported to be oncogenic. In the present study, we have isolated a novel oncogene that has signi®cant homology with Ral-GDS (Ral guanine dissociation stimulator) (Albright et al, 1993), a molecule that has been shown to be also a Ras e ector (Hofer et al, 1994;Spaargaren and Bischo , 1994). We named this oncogene rgr for Ral-GDS related.…”
Section: Introductionmentioning
confidence: 99%
“…In the synapse of rat brain, rapl p21 is found in the synaptic plasma membrane, the synaptic vesicle, and the synaptic mitochondria, while ras p21 is primarily located to the synaptic plasma membrane. Since ralGDS is ubiquitously expressed in various tissues [21], rapl p21 may exert its own specific actions through RGL (ralGDS) in places where rapl p21 alone is expressed. Taken together with the observations that ral p24 is localized to the synaptic vesicle [37], it is intriguing to speculate that the signal from rap 1 p21 to ral p24 through RGL (ralGDS) is important for the function of the synaptic vesicle.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal domain of RGL and ralGDS has been found to associate with the GTP-bound form of ras p21 through the effector loop of ras p21 [20,22,23]. ralGDS stimulates GDP/GTP exchange of ral p24 [21]. ral p24 has been originally isolated by probing with an oligonucleotide corresponding to one of the GTP-binding domain of ras p21 [24].…”
Section: Introductionmentioning
confidence: 99%
“…The exchange of a Ral-bound GDP molecule with GTP, thus activating Ral, is catalyzed by Ralspecific guanine-nucleotide exchange factors (GEFs), which are subdivided into the RalGDS and RalGPS families. Members of the RalGDS family, including RalGDS, Rgl, and Rlf (Albright et al, 1993;Murai et al, 1997;Wolthuis et al, 1997), contain a Ras binding domain (RBD) in their C-terminal region and are proposed to be stimulated by GTP-bound Ras. In contrast, the RalGPS family lacks an RBD in their sequences and may respond to other upstream stimuli independent of Ras activation (de Bruyn et al, 2000;Rebhun et al, 2000;Ceriani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%